An Analysis of the Picture and Picture Learning Model on the Indonesian Language Achievement of Second Grade Students at SDN 09 Sitiung - Nanda, Dodi Widia; Darniyanti, Yulia; Saputri, Mariska Fajar (The Future of Education Journal, 2025)
This study was motivated by the low learning outcomes in Indonesian language among second-grade elementary school students. The purpose of this research was to explore teachers' perceptions regarding the implementation of the Picture and Picture model in response to these low learning outcomes. Data were collected using several techniques: observation, interviews, and documentation. The data analysis process included the stages of data collection, data reduction, data presentation, and conclusion drawing (verification). To ensure data validity, source triangulation and technique triangulation were employed. The results of the study revealed that the use of the Picture and Picture model improved students' learning outcomes. Through image-based media, students found it easier to understand the material, making the learning process more effective and enjoyable. Therefore, this model is highly effective for teaching Indonesian language in lower grade levels.